BCS Model Hamiltonian of the Theory of Superconductivity as a Quadratic Form - Petrina, D. Ya. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
Bogolyubov proved that the average energies (per unit volume) of the ground states for the BCS Hamiltonian and the approximating Hamiltonian asymptotically coincide in the thermodynamic limit. In the present paper, we show that this result is also true for all excited states. We also establish that, in the thermodynamic limit, the BCS Hamiltonian and the approximating Hamiltonian asymptotically coincide as quadratic forms.